AES and XPS characterization of TiN layers formed and modified by ion implantation - Melnik, V.; Popov, V.; Kruger, D.; Oberemok, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Compositional characterization of sputtered and implanted titanium nitride (TiN) layers for microelectronics application is performed based on Auger Electron Spectroscopy (AES) and X-ray induced Photoelectron Spectroscopy (XPS) data. AES shows a strong overlapping of the most intensive peaks of Ti and N. A simple empirical method using intensity relations of Auger spectra is developed for quick estimation of layer composition in small areas. Defined modification of the TiN layers was realized by means of carbon and oxygen implantation to study their influence on quantitative analysis. In difference to standard AES analysis the results of quantification using the method proposed are found to be in good agreement with XPS profiles and with results from Principal Component Analysis (PCA), where peak overlapping is excluded. The influence of oxygen was found to be crucial for standard AES analysis but it could be taken into account in the proposed method. High carbon concentrations show no significant influence on the Ti and N peak shapes.